Microbiological quality of bulk tank raw milk from two dairy farms in Hajdú-Bihar County, Hungary - Kojo Woode, Benjamin; Petróczki, Flóra; Béri, Béla; Peles, Ferenc (Acta Agraria Debreceniensis, 2018)
Two main channels have been identified to be responsible for microbiological contamination of raw milk and milk products. Firstly, contamination has occurred due to udder infection from the cow or the blood which harbours most bacteria that come in contact with the raw milk. Secondly, via external factors (may include faeces, skin, contaminated water, environment etc.) which are associated with the operation of milking. There is direct contact with the milk and/or surfaces before, during or after the milking, posing public health risk and economic decline. The aim of this study was to examine the bacteriological quality of bulk tank raw milk samples collected from two different size dairy farms (Farm 1 and Farm 2) of different housing forms (cubicle loose and deep litter) in Hajdú-Bihar County, Hungary in July, 2017. Three samples were taken from each farm, and the total plate count, coliform count, Escherichia coli count, Staphylococcus aureus count, and yeast and mould count were determined in them.The results clearly showed low level of all measured bacteria group load in Farm 1 samples in comparison to Farm 2 with the exception of coagulase-negative Staphylococcus (CNS) which represented high level in general, indicating significant difference (P